2023
DOI: 10.3390/cells12131780
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of the Pathogenesis of Cardiac Hypertrophy

Abstract: Pathological cardiac hypertrophy is a key risk factor for the development of heart failure and predisposes individuals to cardiac arrhythmia and sudden death. While physiological cardiac hypertrophy is adaptive, hypertrophy resulting from conditions comprising hypertension, aortic stenosis, or genetic mutations, such as hypertrophic cardiomyopathy, is maladaptive. Here, we highlight the essential role and reciprocal interactions involving both cardiomyocytes and non-myocardial cells in response to pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 340 publications
1
7
0
Order By: Relevance
“…The factors that determine these divergent trends in ACE2 protein expression in cardiomyocytes and non-cardiomyocytes are unclear. However, it is most likely associated with myocardial remodeling characteristics, where the capillary network becomes inadequate during the hypertrophy of cardiomyocytes [51,52]. This could be supported by a significant negative correlation between the ACE2 immunostaining score in non-cardiomyocytes and the left ventricular mass documented in our study.…”
Section: Discussionsupporting
confidence: 71%
“…The factors that determine these divergent trends in ACE2 protein expression in cardiomyocytes and non-cardiomyocytes are unclear. However, it is most likely associated with myocardial remodeling characteristics, where the capillary network becomes inadequate during the hypertrophy of cardiomyocytes [51,52]. This could be supported by a significant negative correlation between the ACE2 immunostaining score in non-cardiomyocytes and the left ventricular mass documented in our study.…”
Section: Discussionsupporting
confidence: 71%
“…Due to haemodynamic overload and subsequent mechanical stress, mostly cardiomyocytes, but other cardiac cell types also, release autocrine and paracrine factors such as hormones, cytokines, growth factors (GFs), and chemokines. These factors, that may be meant to contribute to the adaptation to stress, when sustained, become maladaptive mediators contributing to decompensation to heart failure (reviewed in 58 , 59 ).…”
Section: Non-cardiomyocyte Eventsmentioning
confidence: 99%
“…At the same time, the immune response is one of the important reasons for the development of HCM. Numerous studies have shown that HCM patients have leukocyte infiltration and elevated levels of inflammatory cytokines in their myocardium, which may be key factors in the progression of HCM to the end stage of heart failure [ 7 ]. In addition, the genetic deficiency of the key inflammatory cytokine IL-6 has been shown to alleviate TAC-induced left ventricular dysfunction and hypertrophy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%